Domestic, industrial, (en)closed? Survey and excavation of a Late Bronze Age/Early Iron Age promontory enclosure at Gob Eirer, Lewis, Western Isles - Nesbitt, Claire; Church, Mike J; Gilmour, Simon M D (Proceedings of the Society of Antiquaries of Scotland, 2012)
This is the first of four papers that present the results of survey and excavations undertaken in the late 1990s as part of the Uig Landscape Project on Lewis in the Western Isles (Na h-Eileanan Siar). This paper introduces the project and presents the results of the survey and excavations on the promontory enclosure of Gob Eirer, one of the earliest of the Uig sites excavated. Gob Eirer is located on a stack just off the Uig shoreline in the Camas Uig, connected to the mainland by a pebble beach. The results of the excavations are discussed in terms of the structural form, stratigraphy, material culture and environmental evidence from the site. Gob Eirer is then considered within the wider context of the Late Bronze Age and Early Iron Age archaeology of Atlantic Scotland and broader research themes surrounding promontory enclosures.